Building information modelling adoption in Uganda’s construction industry - Acheng, Pamela O.; Kibwami, Nathan; Mukasa, Tom J.; Odongkara, Brian B.; Birungi, Rachel; Semada, Julius; Manga, Musa (Informa UK Limited, 2022)
Building Information Modelling (BIM) has gained traction over the last decade seeing several countries making BIM mandatory. Projects using BIM have enjoyed better quality, reduced costs, and duration. However, its adoption remains low in developing nations like Uganda. This study assessed the state of BIM and its feasibility in Uganda’s construction industry. Data was collected using a structured online survey from 162 registered Architecture, Construction, and Engineering professionals. The analysis applied statistical tests like One-way non-parametric ANOVA, pairwise post hoc dunn and Mann-Whitney tests to assess relationships between profession, work experience, role in the supply chain, involvement in academia, against the awareness, BIM tools used, BIM functions, perceived benefits of BIM, and barriers to BIM adoption. Enhanced productivity was the highest benefit of BIM, along with complete project information and improved design quality. Acquisition and training costs were the top barriers to adoption. The ANOVA test showed those in academia had better understanding of BIM concepts, implying academia's importance in promoting BIM while work experience influenced BIM functions used and awareness of BIM tools. Different professions had varied understanding of some BIM concepts.